The determining factors of Ecuadorian economic growth from an endogenous growth perspectiv - Escobar-Olmedo, Jonathan Lenin (2025)
This case study investigates the determinants of economic growth in Ecuador during the period 2001-2019, using an endogenous growth approach, employing multiple linear regression analysis complemented with the statistical model of growth accounting. The study revealed that several factors played significant roles in Ecuadorian economic growth during the period analyzed. A positive and statistically significant relationship was found between public and private physical capital investment, public spending and GDP. In addition, it was observed that employment and human capital contributed significantly to the country's economic growth. The results suggest the importance of policies that encourage both public and private infrastructure investment, as well as public spending directed to key areas of development. In addition, they highlight the relevance of policies that promote employment and the improvement of human capital to boost sustained economic growth in Ecuador.